E-035 Symptomatic Fusiform Basilar Artery Aneurysm: "Kissing" Stent Reconstruction. (26th July 2014) - Shownkeen, H; Hall, M; Doerr, A; Ortiz, C
Abstract : Introduction: A case presentation of the treatment of a large-giant, symptomatic, fusiform basilar artery aneurysm using kissing telescopic stents. The patient is a 53 year old male who presented for further evaluation of a giant fusiform basilar artery aneurysm which was found on MRI obtained for headache and bilateral upper extremity numbness and tingling. Materials and methods: The patient underwent diagnostic cerebral angiogram with 3D rotational angiography confirmed the giant vertebrobasilar aneurysm measuring 19 x 35 mm extending from the basilar confluence to just beyond the basilar perforators. The initial intervention plan was staged kissing telescopic stenting of the aneurysm to provide a framework for subsequent coil embolization of the aneurysm sac. Results: Utilizing bilateral vertebral artery access, 8 telescoping Codman Enterprise stents were simultaneously deployed by two operators in a kissing fashion beginning distally at the posterior cerebral arteries with proximal extension to the vertebral arteries (distal to PICA). Cerebral angiogram was repeated at 8 weeks with the intent to embolise the aneurysm sac with coils. Angiography demonstrated significant decrease of the aneurysm flow channel, presumably related to flow diversion. CTA and subsequent MRI confirmed decrease in aneurysm flow channel and overall aneurysm size with interval sac thrombosis. Given these imaging findings in the setting of clinical improvement, additional coil embolization was not pursued. Additional follow up imaging at 6 and 15 months demonstrated further decrease in aneurysm sac size and flow channel. Clinically the patient is independent with no further neurologic events or decline. Conclusion: We present a novel, endovascular stenting technique (without coil embolization) for successfully treating symptomatic, giant basilar artery aneurysms. Disclosures: H. Shownkeen: None. M. Hall: None. A. Doerr: None. C. Ortiz: None.